The effects of global postural re-education on sleep quality and stress in university women lecturers: a randomized controlled trial - Rodríguez-Aragón, Manuel; Barranco-Rodríguez, David; de Mora-Martín, Marta; Sánchez-Jorge, Sandra; Varillas-Delgado, David; Valle-Benítez, Noelia (Frontiers in Psychiatry, 2024)
Objective: The purpose of this study was to evaluate the effect of Global Postural Re-education (GPR) on sleep quality and stress in health sciences women lecturers. Methods: 24 women University lecturers were allocated in this randomized controlled trial into intervention (n = 12) and control group (n = 12). The intervention group underwent familiarization and training on the therapy to execute 8-weeks treatment with GPR. Data collected on sleep quality were analyzed using 24h accelerometry (Actigraphy GT3X+) in addition to the Pittsburgh questionnaire score (PSQI) as well as by the State-Trait Anxiety Inventory (STAI) anxiety questionnaire. Data on stress were collected by measuring salivary cortisol. Results: After comparing the GPR of the groups, there was a main effect of group (F = 5.278, p = 0.044) for PSQI. The post hoc analysis revealed that both groups decreased scores between pre-and post-treatment. Additionally, in post-treatment, there was differences between groups. For sleep latency, there were a main effect of group (F = 6.118, p = 0.031) and score x group (F = 9.343, p = 0.011) interactions. The post hoc analysis revealed that treatment group decreased scores between pre-and post-treatment and there was differences between groups (all p < 0.050). Conclusion: The self-administered GPR improves sleep quality in women University lecturers, providing a valuable self-regulation tool for enhanced sleep quality to enhanced academic performance. Further study may help to develop this as a potential tool to help university lecturers job performance.